Ciphers and Executioners: How 3′-Untranslated Regions Determine the Fate of Messenger RNAs - Mayya, Vinay K.; Duchaine, Thomas F. (Frontiers in Genetics, 2019)
The sequences and structures of 3′-untranslated regions (3′UTRs) of messenger RNAs govern their stability, localization, and expression. 3′UTR regulatory elements are recognized by a wide variety of trans-acting factors that include microRNAs (miRNAs), their associated machinery, and RNA-binding proteins (RBPs). In turn, these factors instigate common mechanistic strategies to execute the regulatory programs encoded by 3′UTRs. Here, we review classes of factors that recognize 3′UTR regulatory elements and the effector machineries they guide toward mRNAs to dictate their expression and fate. We outline illustrative examples of competitive, cooperative, and coordinated interplay such as mRNA localization and localized translation. We further review the recent advances in the study of mRNP granules and phase transition, and their possible significance for the functions of 3′UTRs. Finally, we highlight some of the most recent strategies aimed at deciphering the complexity of the regulatory codes of 3′UTRs, and identify some of the important remaining challenges.